Densidade de estocagem e restrição alimentar em juvenis de piapara - Gonçalves, André Fernando Nascimento [UNESP]; Ha, Natalia [UNESP]; Biller-Takahashi, Jaqueline Dalbello [UNESP]; Sato, Leonardo Seiji [UNESP]; Kishimoto, Marcio Kazuaki [UNESP]; Takahashi, Leonardo Susumu [UNESP] (My University, 2014)
The effects of stocking density and food restriction in juvenile piapara (Leporinus elongatus) were studied by two experiments. In the first, 88 piaparas juveniles were stocked in three densities (0.13, 0.20 and 0.40 fish L-1) for 70 days. Were evaluated: weight gain, average consumption, specific growth rate and feed conversion. The experiment was conducted in completely randomized design with three treatments (0.13, 0.20 and 0.40 fish L-1) and four replicates. In the second experiment, 84 fish were divided into three treatments (RBD, with 4 replicates): control group (daily food); FDS group (animals fed on weekends) and Res 21 group (animals subjected to food restriction for 21 days). Highest stocking density resulted highest biomass produced. Fish subjected to food restriction for 21 days and animals fed on weekends group, displayed full compensatory growth.
Stocking density and food restriction of piapara juvenile
Keywords: Compensatory growth; Leporinus sp; Management